Universities of the Third Age in Poland: Emerging Model for 21st Century - Andrzej Klimczuk (Journal of Education, Psychology and Social Sciences, 2013)
Main objective of this paper is to describe emergence of a Polish Universities of the Third Age model. These are a multidisciplinary non-formal education centers, which allow formation of positive responses to the challenges of an ageing population. Article indicates main organizational changes of these institutions conditioned by internal and external factors. Essay describes transformation, differentiation factors, and characteristics of these institutions for elderly based on a critical analysis of literature.
Keywords: H75; I20; J11; J14; 330; creative ageing policy; Third Age Universities; standardization; fourth age; silver economy; Education